2017
DOI: 10.1111/cei.12954
|View full text |Cite
|
Sign up to set email alerts
|

The identification of up-regulated ebv-miR-BHRF1-2-5p targeting MALT1 and ebv-miR-BHRF1-3 in the circulation of patients with multiple sclerosis

Abstract: Epstein-Barr virus (EBV) is a well-documented aetiological factor for multiple sclerosis (MS). EBV encodes at least 44 microRNAs (miRNAs) that are readily detectable in the circulation of human. Previous studies have demonstrated that EBV-encoded miRNAs regulate host immune response and may serve as biomarkers for EBV-associated diseases. However, the roles of EBV miRNAs in MS are still unknown. To fill the gap, we conducted a comprehensive profiling of 44 mature EBV miRNAs in 30 relapsing-remitting MS (RRMS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 49 publications
(58 reference statements)
1
28
0
Order By: Relevance
“…These EBV-encoded miRNAs have also been shown to be important regulators for host-pathogen interactions and viral carcinogenesis (33). In different host cells, the expression profile of these viral miRNAs could be different and may serve as biomarkers for EBV-associated diseases (34)(35)(36)(37). Consistent with previous studies, which showed that the expression of miRNA from the miR-BHRF1 cluster was relatively restricted to lytic and latency III phases of EBV-infected B lymphoma cells (36,(38)(39)(40)(41)(42), we also observed that the miR-BHRF1 cluster is highly expressed in EBV-immortalized LCL cells and responds to LA treatment.…”
mentioning
confidence: 99%
“…These EBV-encoded miRNAs have also been shown to be important regulators for host-pathogen interactions and viral carcinogenesis (33). In different host cells, the expression profile of these viral miRNAs could be different and may serve as biomarkers for EBV-associated diseases (34)(35)(36)(37). Consistent with previous studies, which showed that the expression of miRNA from the miR-BHRF1 cluster was relatively restricted to lytic and latency III phases of EBV-infected B lymphoma cells (36,(38)(39)(40)(41)(42), we also observed that the miR-BHRF1 cluster is highly expressed in EBV-immortalized LCL cells and responds to LA treatment.…”
mentioning
confidence: 99%
“…miRs can have multiple targets as a result of binding not requiring 100% complementarity. 70 EBV miR-BHRF1-2-5p inhibits the MALT1 gene, which is a known regulator of immune homeostasis, 71 as well as the B-cell differentiation regulator/tumor suppressor gene PRDM1/BLIMP1, 72 but it was not previously known to bind PD-L1 or PD-L2. Using an integrated approach, we predicted and subsequently validated the interaction between EBV miR-BHRF1-2-5p with the 39UTRs of both PD-L1 and PD-L2.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, EBV miR-BHRF1-2-5p has been reported to target mucosa-associated lymphoid tissue lymphoma transport protein 1 (MALT1), a key regulator of immune homeostasis (Wang et al, 2017). EBV miR-BART16 interferes with the type I IFN signaling pathway by directly targeting cAMP response element-binding protein (CREB)-binding protein (CREBBP), a key transcriptional coactivator in IFN signaling (Hooykaas et al, 2017).…”
Section: Ebv-encoded Mirnas Regulate the Immune Response By Targetingmentioning
confidence: 99%